Social desirability bias in attitudes towards sexism and DEI policies in the workplace - Anne Boring; Josse Delfgaauw (Tinbergen Institute, 2024)
Do workers speak their mind about sexism and about diversity, equity, and inclusion (DEI) policies in the workplace? We measure social desirability bias regarding sexism and DEI policies using a list experiment survey among workers from five male-dominated industries in France and in the US. In both countries and, remarkably, among both men and women, we document substantial social desirability bias. Managers exhibit a larger bias than non-managerial employees. This difference between voiced and real attitudes may make organizations overestimate support for DEI policies in their workforce, rendering such policies less effective.
Keywords: J16; J71; M14; M5; 330; Sexism; Diversity; Social desirability bias; List experiment survey